2013
DOI: 10.1242/jeb.080879
|View full text |Cite
|
Sign up to set email alerts
|

Costs of colour change in fish: food intake and behavioural decisions

Abstract: SUMMARYMany animals, particularly reptiles, amphibians, fish and cephalopods, have the ability to change their body colour, for functions including thermoregulation, signalling and predator avoidance. Many fish plastically darken their body colouration in response to dark visual backgrounds, and this functions to reduce predation risk. Here, we tested the hypotheses that colour change in fish (1) carries with it an energetic cost and (2) affects subsequent shoal and habitat choice decisions. We demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…Therefore, metabolic costs and other constraints associated with changing colour and maintaining chromatophore state may be important. One study has at least demonstrated that when guppy fish ( Poecilia reticulata ) are induced to change colour by altering the background, individuals increase their food consumption levels [21]. The implication is that increased food consumption occurs to offset the energetic costs of changing colour.…”
Section: Mechanisms and Control Of Colour Changementioning
confidence: 99%
“…Therefore, metabolic costs and other constraints associated with changing colour and maintaining chromatophore state may be important. One study has at least demonstrated that when guppy fish ( Poecilia reticulata ) are induced to change colour by altering the background, individuals increase their food consumption levels [21]. The implication is that increased food consumption occurs to offset the energetic costs of changing colour.…”
Section: Mechanisms and Control Of Colour Changementioning
confidence: 99%
“…Such “matching habitat choice” thus allows individuals to be an agent instead of a target of selection and thereby exerts a distinct evolutionary force that can lead to adaptive evolution, even in the absence of natural selection (Bolnick & Otto, ; Edelaar & Bolnick, ). Empirical evidence for matching habitat choice is still limited, yet, some studies have shown that, for example, different phenotypes disperse and settle preferentially in habitats where they are more camouflaged (Dreiss et al., ; Gillis, ; Karpestam, Wennersten, & Forsman, ; Rodgers, Gladman, Corless, & Morrell, ) or more physiologically adapted (Bestion, Clobert, & Cote, ; Jacob et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…flounders, soles) and other bottom dwellers prefer to settle on sands or painted tank areas with background coloration and patterning similar to their own (Sumner, 1911(Sumner, , 1935Mast, 1914;Hewer, 1930;Fairchild & Howell, 2004;Ryer et al, 2008). Freshwater guppies and least killifish also prefer certain backgrounds (Kjernsmo & Merilaita, 2012;Rodgers et al, 2013). Among terrestrial animals, moths show a preference for backgrounds with colours similar to their own (Kettlewell & Conn, 1977;Steward, 1977;Endler, 1984) and they position their bodies to maximize crypsis (Webster et al, 2009;Kang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%